A New Approach to the Creation of Linguistic Dictionaries - Adiba Botirova Erkinovna (Research Parks Publishing LLC, 2021)
The article is about the creation of electronic dictionaries based on the classification of parts of speech, which is a new approach in Uzbek lexicography, teaching both spelling and pronunciation, used in the educational process, as well as in philological research, office work and documentation.